2013
DOI: 10.1016/j.carbpol.2013.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on the surface properties and morphology of ground flax

Abstract: Flax fibers were ground with a ball-mill and four fractions with different size ranges were collected by sieving. These were tested for water sorption, degree of polymerization (DP), copper number, hydroxyl number and analyzed by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and inverse gas chromatography (IGC). Significant differences were found between the properties of the flax fiber and those of the ground versions, including fragmentation of fibers, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Based on the X-ray diffraction analysis of fibres and their ground powders it was assumed that the reason of unreal surface energies can be the less effective adsorption of probes on the less perfect crystalline surface of ground samples. Results of the next comprehensive study on ground flax of different size confirmed our statement that the multicellular and multicomponent flax is very susceptible to grinding and undergoes complex chemical and physical changes [22]. All the applied methods revealed differences in properties of the fibrous and ground flax, and the results showed that dispersion components of surface tensions measured by IGC depends on several parameters (not only on surface energy) which influence the adsorption of probe molecules on the surface of 5 investigated samples.…”
Section: Introductionsupporting
confidence: 65%
“…Based on the X-ray diffraction analysis of fibres and their ground powders it was assumed that the reason of unreal surface energies can be the less effective adsorption of probes on the less perfect crystalline surface of ground samples. Results of the next comprehensive study on ground flax of different size confirmed our statement that the multicellular and multicomponent flax is very susceptible to grinding and undergoes complex chemical and physical changes [22]. All the applied methods revealed differences in properties of the fibrous and ground flax, and the results showed that dispersion components of surface tensions measured by IGC depends on several parameters (not only on surface energy) which influence the adsorption of probe molecules on the surface of 5 investigated samples.…”
Section: Introductionsupporting
confidence: 65%
“…Size, zeta potential and surface morphology of NPs. Cellular uptake, drug release, in vivo pharmacokinetics and biodistribution are closely related to particle size and surface properties, 49 dynamic light scattering (DLS) was used to measure the size and size distribution of the DTX-loaded NPs, and the data is shown in Table 2. The mean hydrodynamic size of the DTX-loaded NPs was about 90-140 nm in diameter.…”
Section: Formulation and Characterization Of Npsmentioning
confidence: 99%
“…20 % reduction using a grinder. Csiszár et al [70] used a ball mill grinder and observed reduction in crystallite sizes from 5.8 to 4.6 nm, relatively a reduction of 21 %, with flax fiber. These reported levels are somewhat larger than those in this study.…”
Section: Discussionmentioning
confidence: 97%